Molten pool behavior and effect of fluid flow on solidification conditions in selective electron beam melting (SEBM) of a biomedical Co-Cr-Mo alloy - Zhao, Yufan; Koizumi, Yuichiro; Aoyagi, Kenta; Wei, Daixiu; Yamanaka, Kenta; Chiba, Akihiko (Additive manufacturing, 2019)
Selective electron beam melting (SEBM) is a type of additive manufacturing (AM) that involves multiple physical processes. Because of its unique process conditions compared to other AM processes, a detailed investigation into the molten pool behavior and dominant physics of SEBM is required. Fluid convection involves mass and heat transfer; therefore, fluid flow can have a profound effect on solidification conditions. In this study, computational thermal-fluid dynamics simulations with multi-physical modeling and proof-of-concept experiments were used to analyze the molten pool behavior and resultant thermal conditions related to solidification. The Marangoni effect of molten metal primarily determines fluid behavior and is a critical factor affecting the molten pool instability in SEBM of the Co–Cr–Mo alloy. The solidification parameters calculated from simulated data, especially the solidification rate, are sensitive to the local fluid flow at the solidification front. Combined with experimental analysis, the results presented herein indicate that active fluid convection at the solidification front increase the probability of new grain formation, which suppresses the epitaxial growth of columnar grains.